TAFSIR QS. AT-THARIM AYAT 6 DAN HADIST NABI TENTANG TANGGUNG JAWAB ORANG TUA SEBAGAI LANDASAN TEOLOGIS KOLABORASI ANTARA KONSELOR DAN KELUARGA DALAM LAYANAN BIMBINGAN DAN KONSELING ISLAMI DI SEKOLAH - Putri Rahmadani; Emmi Kholilah Harahap; Rifanto Bin Ridwan (STKIP Subang, 2026)
This study aims to analyze the interpretation of QS. At-Tahrim verse 6 and the Prophet’s hadith concerning parental responsibility as a theological foundation for collaboration between counselors and families in Islamic guidance and counseling services at schools. The research employed a library research method with a descriptive-analytical approach through the study of the Qur’an, hadith, tafsir books, and relevant scientific journals. The findings indicate that QS. At-Tahrim verse 6 emphasizes the obligation of parents to protect and educate their families through the cultivation of faith, morality, and spiritual development. The Prophet’s hadith also explains that every parent is a leader who will be held accountable for the education of their children. In the perspective of Islamic guidance and counseling, the family is the first madrasa that greatly influences students’ development. Therefore, school counselors need to establish cooperation with parents in character building, behavioral supervision, and students’ spiritual assistance. Such collaboration can be implemented through regular consultations, Islamic parenting programs, home visits, and intensive communication between schools and families. This study concludes that QS. At-Tahrim verse 6 and the Prophet’s hadith serve as important theological foundations for strengthening Islamic guidance and counseling services based on collaboration between families and schools in order to shape students with noble character and strong religiosity.